2020
DOI: 10.1155/2020/8583540
|View full text |Cite
|
Sign up to set email alerts
|

Solid Dispersion Pellets: An Efficient Pharmaceutical Approach to Enrich the Solubility and Dissolution Rate of Deferasirox

Abstract: Deferasirox (DFX) is an oral iron-chelating agent and classified into class II of the Biopharmaceutics Classification System. Low bioavailability of the drug due to insufficient solubility in physiological fluids is the main drawback of DFX. The idea of the current study was to explore the potential of solid dispersion (SD) as an effective method to improve the dissolution rate of DFX in pellets. The SDs were made by the solvent evaporation technique using polyethylene glycol 4000 (PEG 4000) and polyvinylpyrro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The n value showed that the dominated mechanism of drug release was diffusion as the n value is close to 0.45. Diffusional exponent (n) between 0.45 and 0.89 indicates non-Fickian transport release mechanism [20,21]. As mentioned previously, the addition of the cholesterol in the formulation acts as a stabilizer and decreases the leakage [22].…”
Section: Discussionmentioning
confidence: 91%
“…The n value showed that the dominated mechanism of drug release was diffusion as the n value is close to 0.45. Diffusional exponent (n) between 0.45 and 0.89 indicates non-Fickian transport release mechanism [20,21]. As mentioned previously, the addition of the cholesterol in the formulation acts as a stabilizer and decreases the leakage [22].…”
Section: Discussionmentioning
confidence: 91%
“…The data of SD showed the greatest correlation with the Korsmeyer-Peppas model due to the higher R 2 value (0.916). The goodness of fit of the dissolution behavior of various SDs with the Korsmeyer-Peppas model has been reported by various authors [37,89,90]. The mechanism of release was investigated from the Korsmeyer-Peppas model by fitting 60% of the initial dissolution data.…”
Section: In-vitro Dissolution and Release Kineticsmentioning
confidence: 92%
“…The dried sample was grounded with KBr and compressed into a suitable-size disk (13 mm), then placed inside the apparatus for IR spectroscopy. 22 …”
Section: Methodsmentioning
confidence: 99%